Exploratory Studies on Growth of Saussurea lappa Clarke Cultivated under Mid-hill Sub-humid Zone of Himachal Pradesh Using Growth Hormones - Nayyar, Harsh; Kaushal, S. K. (Indian Forester, 2003)
No abstract